NARRATIVE LEGENDS AS A TOOL FOR IMPROVING READING COMPREHENSION IN 11TH GRADE AT SMK WIRATAMA 45.2 WONOSOBO - Cindy Virginia Adella D; Firdaus Setyarta; Adilla (Merwin Publisher, 2024)
This study aims to explore the use of narrative text as a tool to improve the reading skills of grade 11 students in vocational schools. This activity was carried out in the framework of a Field Experience Program (PPL) with a classroom action approach consisting of two cycles. Each cycle included narrative text learning that involved analyzing legendary stories. The results showed significant improvement in students' reading ability, especially in text comprehension, narrative structure recognition, and vocabulary acquisition. In addition, students' interest in reading also increased. Based on these findings, it can be concluded that narrative texts are effectively used to improve grade 11 students' reading ability.